Comparative analysis of one-time hash-based signatures - Semenets, Valerii; Marukhnenko, O.S.; Gorbenko, I.D.; Khalimov, G.Z. (Radiotekhnika, 2020)
Hash-based signatures are a wide class of post-quantum cryptographic algorithms, their security is based on the complexity of collision and preimage search problems for cryptographic hash functions. The main advantages of this class are post-quantization, easy modification and a well-researched mathematical base. The disadvantages are large sizes of signatures and limited number of uses of one key pair. The most promising algorithms of this class include algorithms of the SPHINCS type, which have a complex structure, including, among others, a one-time Winternitz signature. The paper analyzes the existing one-time signature algorithms, both well-known Lamport and Winternitz schemes, taking into account modifications of the latter one, and alternative methods. An analysis of the security of modified algorithms has been shown, which showed that their security is based on the same mathematical basis as the security of the original algorithms. The one-time use requirement remains critical to the safety of each of the algorithms studied. The sizes of keys and signatures and computational complexity of various algorithms are compared, in what their basic differences consist. The modified algorithms do not add fundamentally new components in cryptosystems but they make it possible to achieve a certain optimization, shifting the conditions of space-time compromise. The extended Lamport signature is of a particular interest, having the same computational complexity and key sizes as the original algorithm, and at the same time allowing one to halve the signature size. In the context of the SPHINCS cryptosystem, the Winternitz signature remains the best option, since it allows the complete computation of the public key directly from the signature.